Healthy live birth following ICSI with retrograde ejaculated cryopreserved sperm - Barkat Ali, Neelam; Ahmed , Maria; Khan, Safdar; Iqbal , Anila; Paul, Sadia (International Journal of Endorsing Health Science Research, 2019)
Background: Retrograde ejaculation is a medical condition that occurs when semen enters the urinary bladder (retrograde) during orgasm instead of passing through the penis (antegrade). Complete retrograde semen flow causes male infertility. An advanced technique intracytoplasmic sperm injection (ICSI) can be used to achieve fertilization in the case of male sub-fertility e.g. Oligo-Astheno-Teratozoospermia. Case Presentation: A couple with primary infertility visited the concept fertility centre, where male was diagnosed with retrograde ejaculation for which ICSI was offered with back-up semen freezing after an initial semen analysis. Management & Results: Female was stimulated with long stimulation protocol and thirteen matured eggs were injected by cryopreserved sperms extracted from urine sediment. Fertilization occurred in twelve eggs out of which two good quality embryos were transferred after day five in vitro culturing and rest were vitrified. The patient conceived triplets and gave birth at 33 weeks, but two babies had neonatal death within four days and the patient has one healthy baby girl. Conclusion: Applying assisted reproductive techniques to aid pregnancy in cases of retrograde ejaculation has paucity of knowledge in Pakistan and this case report is the first in Pakistan to describe the diagnosis and successful treatment of infertile couples, with advanced reproductive technology, where the male partner suffered from retrograde ejaculation.